Evidence of mid- to late-Holocene explosive rhyolitic eruptions from Chaitén Volcano, Chile - Sebastian F.L. Watt; David M. Pyle; Tamsin A. Mather (Andean Geology, 2013)
The 2008 eruption of Chaitén Volcano was widely cited as the first activity at the volcano for over 9000 years. However, we have identified evidence from proximal pyroclastic deposits for three additional explosive eruptions of Chaitén within the past 5000 years. Chaitén has therefore produced at least five explosive eruptions in the Holocene, making it among the most active volcanoes, in terms of explosive output, in the southern part of the Andean Southern Volcanic Zone. All of the five identified Holocene explosive eruptions produced homogeneous high-silica rhyolite, with near identical compositions. Based on our pyroclastic sequence, we suggest that the largest-volume Holocene eruption of Chaitén occurred at ~4.95 ka, and we correlate this with the Mic2 deposit, which was previously thought to originate from the nearby Michinmahuida Volcano.